OPEN EDUCATIONAL RESOURCES - Syaifudin, Mokhamad (Department of English Language Education, UIN Sunan Ampel Surabaya, 2016)
In this article a brief exposition of what open education resources is presented. The article begins by presenting the general idea of what OER is then move to the possible benefits and challenges to the OER for teaching and learning. Efforts to address the possible challenges in OER are also presented as well as the places where OER can be sought. In the end of the article samples of possible scenario of how to use the OER for teaching learning process are also detailed.